PEMBELAJARAN MENULIS SURAT DINAS PADA SISWA KELAS VII SMP NEGERI 11 PONTIANAK - Ilahi, Ayu Kurnia; Priyadi, Antonius Totok; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSMPN 11 Pontianak has recently implemented the 2013 Curriculum. This research discussed the implementation, difficultief student, and evaluation in implementing the curriculum in the Indonesian language subject. This study aims to describe learning to write official letter in class VII students of SMP Negeri 11 Pontianak. The research method used is descriptive in the form of qualitative research. The dataÂ sources in this study were teachers and students. The theory used as the reference in this study is the theory of Indonesian language learning based on the 2013 curriculum. Based on the findings, it was concluded that (1) plans designed by the teacher were in accordance with the 2013 curriculum, (2) the implementation of learning write official letters conducted by teachers based on Teacher Ability Assessment Tool 2 (APKG 2) has been implemented well, and (3) assessment of the learning of write official letters conducted by the teacher is in accordance with the assessment provisions based on the 2013 curriculum.Â Keywords: Learning Instruction, Writing official letters